Petera L. Bergera przejście od teorii sekularyzacji do teorii desekularyzacji - Mariański, Janusz (Humaniora. Czasopismo Internetowe, 2021)
In this paper I present the evolution of views of the american sociologist Peter L. Berger which is a transition from the theory of secularization into the theory of desecularization. He was one of the major representatives of the secualrization paradigm and since the 1990’s he became the creator and adherent of the desecularization paradigm. Desecularization means a persistent and strong presence of religion in the modern world or as a social process it is a reverse version of secularization. According to Berger contemporary sociology of religion should take care of research on the forces affecting mutually secularization and desecularization because “antisecularism is a phenomenon just as important in the modern world as secuarlization.” Berger until the end of 1970’s did focus on the analysis of the secularization processes and later on he commited his research to the issue if desecularization processes.